Nuclear disarmament in the third nuclear age. - Pantoliano, Carolina; Crilley, Rhys (International Affairs, 2026)
The concept of the third nuclear age—which is defined by multipolarity and great power competition, collapsing arms control, disruptive new technologies and a deteriorating security environment—has gained considerable traction in nuclear politics, yet its implications for nuclear disarmament remain underexplored. This article addresses this gap by examining statements made at recent Non-Proliferation Treaty meetings and analyses how disarmament is framed by states. We examine how representations of the third nuclear age shape the conditions of possibility for disarmament. First, we show how the nuclear weapon states and their allies use the third nuclear age discourse to reiterate a future-oriented vision of disarmament that marginalizes it as a potential policy option. Second, we show how, despite emphasizing the value of disarmament, states parties to and supporters of the Treaty on the Prohibition of Nuclear Weapons still present it as a solution that stands outside the context of the third nuclear age, rather than as a central development in this new era. Third, we argue that, despite the real crises of the third nuclear age, significant developments on disarmament are integral, rather than marginal, to the third nuclear age. The article contributes to the field of nuclear politics by drawing attention to disarmament as a feature of the third nuclear age that can expose this discourse as unsettled and create opportunities for innovation and change in nuclear policy.